(4Z,6Z,12Z,14Z)-2,10-Dimethyl-2,8,10,16-tetrahydrodipyrazolo[3,4-e:3',4'-l][1,2,4,8,9,11]hexaazacyclotetradecine-4,12-diamine. - Dolzhenko, Anton; Pastorin, G.; Dolzhenko, A.; Tan, G.; Koh, L. (Blackwell Munksgaard, 2009)
The title compound, C12H16N12, is a centrosymmetric molecule which comprises of a hexaaza[14]annulene macrocyclic ring fused with two pyrazole rings. The macrocyclic ring is essentially planar, with an r.m.s. deviation of 0.0381 Å. The electron pairs of the amino groups are delocalized with the conjugated system of the macrocycle. Strong intramolecular N-H...N hydrogen bonds arranged in an S 2 2 (10) graph-set motif are present in the macrocyclic ring. In the crystal, theamino groups act as donors for intermolecular N-H...N interactions with the N atoms of the heterocyclic system, forming a network of two types of extended chains orientedparallel to the [101] and [011] directions. The crystal packing is also stabilized by weak intermolecular C-H...N hydrogen bonds formed between pyrazole C-H groups and N atoms of the macrocyclic ring, running in the [10] direction.